New quantum boundaries for quantum Simpson’s and quantum Newton’s type inequalities for preinvex functions - Muhammad Aamir Ali (Advances in Difference Equations, 2021)
Abstract In this research, we derive two generalized integral identities involving the q ϰ 2 $q^{\varkappa _{2}}$ -quantum integrals and quantum numbers, the results are then used to establish some new quantum boundaries for quantum Simpson’s and quantum Newton’s inequalities for q-differentiable preinvex functions. Moreover, we obtain some new and known Simpson’s and Newton’s type inequalities by considering the limit q → 1 − $q→ 1^{-}$ in the key results of this paper.